Needs of multimorbid heart failure patients and their carers: a qualitative interview study and the creation of personas as a basis for a blended collaborative care intervention - Engelmann, Petra; Eilerskov, Natasja; Thilsing, Trine; Bernardini, Francesco; Rasmussen, Sanne; Löwe, Bernd; Herrmann-Lingen, Christoph; Gostoli, Sara; Andréasson, Frida; Rafanelli, Chiara; Pedersen, Susanne S.; Jaarsma, Tiny; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Involving patients and carers in the development of blended collaborative care (BCC) interventions for heart failure (HF) is recommended but rarely practiced, and research on the patient perspective is scarce. The aim of this study is to investigate patients’ and carers’ care needs and preferences in order to better customize a novel international BCC intervention. Methods: A qualitative study design using framework analysis was employed, applying the EQUATOR standards for reporting qualitative research (SRQR). Semi-structured interviews were conducted in Germany, Italy, and Denmark with patients aged at least 65 years, having HF and at least two other physical diseases, and their carers. Based on these interviews, personas (prototype profiles of patients and carers) were created. Results: Interviews with 25 patients and 17 carers were analyzed. Initially, seven country-specific personas were identified which were iteratively narrowed down to a final set of 3 personas: The one who a) needs and wants support, b) has accepted their situation with HF and reaches out when needed, and c) feels neglected by the healthcare system. Carers relating to the last persona showed high psychological stress and support needs. Discussion: This is the first international qualitative study on patients’ and carers’ needs regarding a BCC intervention using the creation of personas. Across three European countries, interviews revealed three contrasting personas. Instead of providing “one size fits all”-interventions, the results indicate that BCC interventions should offer different approaches depending on individual patient and carer needs. The personas will serve as a basis for the development of a novel BCC intervention within the EU-wide project ESCAPE.